Multiple Religious Belonging and Religious Communities: Exploring a Neglected Dimension - Hendriks, Jonatan (Interreligious studies and intercultural theology, 2022)
This contribution investigates the concept "community" as a previously underexplored dimension of multiple religious belonging (MRB). A review of the MRB approach to multireligiosity reveals there has been paid relatively little attention to community influence and fluid, non-dualistic styles of religious belonging. We argue that these styles of multiple belonging cannot be accounted for by conventional understandings of MRB that assume a "World Religions Paradigm." After reviewing two approaches to this problem, the article explores a rhizomatic approach to MRB and religious communities. To illustrate this approach, a brief review of several Dutch multireligious communities is presented.